Swedish Vocational Adult Education in the Wake of Marketisation - Per Andersson; Karolina Muhrman (European Research Network Vocational Education and Training (VETNET), 2022)
Context: This study is about vocational education and training for adults within municipal adult education (MAE). Sweden has a long tradition of adult education, and has one of the world's highest proportions of participants in adult education. The Swedish education system is characterised by extensive marketisation with many private actors, particularly in adult education. The focus of this article is on the enactment of the market orientation in vocational adult education, with the purpose of showing how vocational adult education is organised in different ways in Swedish municipalities and how national adult education policy is enacted in local VET practices.  Methods: The data consist of documents presenting relevant national policies for adult education, in particular on vocational education, and semi-structured interviews with adult education leaders in 20 municipalities.  Findings: The findings show that MAE in Sweden has a clear labour market focus on offering education that corresponds to working life's labour requirements. Most municipalities have a shortage of staff in elderly care and childcare, which is why they offer a large number of training places in these professions. Many immigrants choose these training programmes to get a job. It is also common for municipalities to offer these training programmes in combination with SFI (Swedish for immigrants). This means that MAE fulfils an important function for integration. VET in MAE is offered as school-based training, apprenticeships or distance education. Offering VET at a distance makes it possible to provide a wider range of training programmes, and enables people who have difficulties participating in on-site training (due to commitments such as work or young children) to take part. Apprenticeship training provides work experience and often leads to employment. However, a weak interest in apprenticeship training among students and difficulties finding apprenticeship placements are examples of reasons why the number of apprenticeships is often very limited.  Conclusion: Swedish MAE is characterised by flexibility and a broad supply of courses. However, there is a clear focus on certain vocational areas - mainly within the municipal organisation. This gives reason to question whether publicly funded VET for adults should mainly prepare participants for publicly funded labour-market sectors, or whether other sectors could also benefit from newly trained adults. Since vocational training within MAE is of great importance for immigrants' establishment in the labour market, there is a risk that unilateral investments in certain vocations will limit immigrants' career opportunities.